La enseñanza de la representación como campo problematizador del proyecto : un estudio de estrategias didácticas y su evaluación - Sanjurjo Caracoche, H. Moira (2019)
The present research studies teaching strategies and evaluation of representation as problematic field of project disciplines. The context in which the work was developed is the initial and predisciplinar field of the Basic and Common Cycle (CBC), for all the courses taken at the Faculty of Architecture, Design and Urbanism (FADU) of the University of Buenos Aires (UBA).\nThe teaching of representation for the project disciplines is supported by a tradition of practice that has accompanied the processes of transformation of thought in general and project disciplines in particular. At present, it is in close relation with the contemporary conceptions about the projective thought that manifests a complex and integrating knowledge.